2020
DOI: 10.21203/rs.3.rs-28610/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of CPR training by social media networks and workshop on CPR skill of nursing and midwifery students

Abstract: Background: Smartphone-based education has been recommended in different areas of medical education. Considering the capabilities and features of social media, this study aimed to investigate the effect of social media and workshop on CPR performance of nursing and midwifery students. Methods: In this quasi-experimental study, 59 nursing and midwifery students were randomly divided into two groups (WhatsApp- and workshop-based training). Students' CPR skill was assessed at four time-points including before the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In their study, Alijanpour et al [22] and Nord et al [23] compared practical education with multimedia education in terms of their effectiveness in improving medical students' learning of CPR and concluded that the group which received education through practice combined with theory was more skillful than the group which received education exclusively from a virtual network, which is consistent with findings of the present study. In their study, Ghorbani et al [24], showed that the mean score of CPR skills in the workshop group was higher than the WhatsApp messenger group.…”
Section: Discussionmentioning
confidence: 90%
“…In their study, Alijanpour et al [22] and Nord et al [23] compared practical education with multimedia education in terms of their effectiveness in improving medical students' learning of CPR and concluded that the group which received education through practice combined with theory was more skillful than the group which received education exclusively from a virtual network, which is consistent with findings of the present study. In their study, Ghorbani et al [24], showed that the mean score of CPR skills in the workshop group was higher than the WhatsApp messenger group.…”
Section: Discussionmentioning
confidence: 90%
“…earning midwifery practice is very important for nursing students to provide professional services. One of the targets for achieving competence in midwifery practice is the ability to provide standard delivery services [1,2]. The ability in this field can increase competence in standard delivery care [3].…”
Section: Introductionmentioning
confidence: 99%